Analysis of English Teachers’ Strategies and perception in Teaching Speaking Online at SMPN 1 Sengkang - Hesti Mutiara; St Asriati Am; Ardiana Ardiana (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to identify the teaching methods used by the English teachers at SMP Negeri 1 Sengkang and how the students perceived those methods. Sengkang served as the location, and a qualitative research design was applied. Three instruments were used in this research, which was a total purposive sampling. The first was an observation checklist for teachers who are instructing online learning. (2) interviewing teachers to learn about their tactics, and (3) interviewing students to see how they view teachers' strategies The study's findings showed that: 1) Three different teaching methods were used by the teachers in online instruction. There were discussions, stories, and dialogues. Because it is based on a manual and is simple to practice online, teachers adopt this technique. Other tactics are occasionally employed by teachers, but they are uncommon because they are ineffective while teaching online. 2) The study's findings demonstrate that all of the teachers' online learning tactics were supported by students' perceptions of those strategies. Students believed that using the tactics in online learning was successful in assisting them in understanding the subject matter. Additionally, pupils are engaged and readily understand the subject when it is presented through the teacher's chosen media.